LEGAL PROTECTION OF WAYANG CENK BLONK BASED ON COPY RIGHT LAW - Dwijayanthi, Indah Triari; Sarjana, I Made (Kertha Semaya : Journal Ilmu Hukum; Vol 9 No 6 (2021), 2021)
The purpose of this scientific paper is to find out the limits of legal regulations on the distribution of video content of wayang cenk blonk which can be categorized as copyright infringement and to find out the form of government coordination in the context of preventing copyright infringement of the wayang cenk blonk as a puppet art on social media. This is a normative legal research with a statutory regulatory approach and conceptual approach. The study shows that the limitation of an act can be catagorized as copyright infringement if the creation and use of the work is carried out without obtaining permission from the Creator or the Copyright Holder. The government has also coordinated in order to prevent copyright infringement of the wayang cenk nlonk on social media by conducting national cooperation regarding the Implementation of Content Closure and/or Access Right to Use of Copyright violations.